Which evidence-based teaching practices change over time? Results from a university-wide STEM faculty development program - Mallory A. Jackson; Sungmin Moon; Jennifer H. Doherty; Mary Pat Wenderoth (SpringerOpen, 2022)
Abstract Background There is overwhelming evidence that evidence-based teaching improves student performance; however, traditional lecture predominates in STEM courses. To provide support as faculty transform their lecture-based classrooms with evidence-based teaching practices, we created a faculty development program based on best practices, Consortium for the Advancement of Undergraduate STEM Education (CAUSE). CAUSE paired exploration of evidence-based teaching with support for classroom implementation over two years. Each year for three years, CAUSE recruited cohorts of faculty from seven STEM departments. Faculty met biweekly to discuss evidence-based teaching and receive feedback on their implementation. We used the PORTAAL observation tool to document evidence-based teaching practices (PORTAAL practices) across four randomly chosen class sessions each term. We investigated if the number of PORTAAL practices used or the amount of practices increased during the program. Results We identified identical or equivalent course offerings taught at least twice by the same faculty member while in CAUSE (n = 42 course pairs). We used a one-way repeated measures within-subjects multivariate analysis to examine the changes in average use of 14 PORTAAL practices between the first and second timepoint. We created heat maps to visualize the difference in number of practices used and changes in level of implementation of each PORTAAL practice. Post-hoc within-subjects effects indicated that three PORTAAL practices were significantly higher and two were lower at timepoint two. Use of prompting prior knowledge and calling on volunteers to give answers decreased, while instructors doubled use of prompting students to explain their logic, and increased use of random call by almost 40% when seeking answers from students. Heat maps indicated increases came both from faculty's adoption of these practices and increased use, depending on the practice. Overall, faculty used more practices more frequently, which contributed to a 17% increase in time that students were actively engaged in class. Conclusions Results suggest that participation in a long-term faculty development program can support increased use of evidence-based teaching practices which have been shown to improve student exam performance. Our findings can help prioritize the efforts of future faculty development programs.